Transvaginal tru-cut biopsy versus ascitic fluid cytology in gynaecologic tumours: A comparative diagnostic study - Munachiso Iheme Ndukwe; Petra Bretova; Ivan Praznovec; Denisa Pohanková; Dominik Karasek; Martin Stepan; Dominik Habes; Jan Laco; Eva Hovorkova; Akaninyene Eseme Ubom; Milan Vosmik; Igor Sirak (PLoS ONE, 2026)
Objective To compare the diagnostic performance- including adequacy, accuracy, safety, sensitivity, specificity, and predicitve values-  of transvaginal tru-cut biopsy and ascitic fluid cytology in women with gynaecologic tumours. Methods A retrospective review was conducted of women with gynaecologic tumours who underwent ultrasound-guided transvaginal tru-cut biopsy and ascitic fluid cytology at the Department of Obstetrics and Gynaecology, University Hospital Hradec Kralove, between January 2018 and December 2021. Results A total of 104 women with gynaecologic tumours underwent transvaginal tru-cut biopsy, of whom 47 also had ascitic fluid cytology. The diagnostic accuracy [93.3% (95% CI: 84.1%−97.4%) vs. 83.9% (95% CI: 67.4%−92.9%)], sensitivity [93.3% (95% CI: 82.1%−97.7%) vs. 79.2% (95% CI: 59.5%−90.8%)], and negative predictive value [82.4% (95% CI: 59.0%−93.8%) vs. 58.3% (95% CI: 32.0%−80.7%)] were higher for transvaginal tru-cut biopsy compared to ascitic fluid cytology. Adequacy [93.3% (95% CI: 86.8%−96.7%) vs. 93.6% (95% CI: 82.8%−97.8%)], specificity [93.3% (95% CI: 70.2%−98.8%) vs. 100.0% (95% CI: 64.6%−100.0%)], and positive predictive value [97.7% (95% CI: 88.2%−99.6%) vs. 100.0% (95% CI: 83.2%−100.0%)] were similar for the two methods. Only one tru-cut biopsy was complicated by bleeding, giving an overall complication rate of 1% (95% CI: 0.2%−5.3%). There was no complication with ascitic fluid cytology. Concordance of tru-cut histopathological diagnoses with ascitic fluid cytological diagnoses was 78% (95% CI: 63.6%−87.5%). Conclusion Ultrasound-guided tru-cut biopsy provides more diagnostic information than ascitic fluid cytology and is the preferred method when feasible. However, ascitic fluid cytology remains a safe and practical option when biopsy is unavailable.